Promise of blood eaudiobook - McClellan, Brian (Powder Mage trilogy,, 2013)
"Just plain awesome" — Brandon Sanderson Civil unrest cripples the citizens of Adro in the aftermath of the revolution that obliterated the monarchy. Now, Field Marshal Tamas and his lieutenants must confront the true cost of freedom in book one of the Powder Mage Trilogy. It's a bloody business overthrowing a king. . . Field Marshal Tamas' coup against his king sent corrupt aristocrats to the guillotine and brought bread to the starving. But it also provoked war with the Nine Nations, internal attacks by royalist fanatics, and the greedy to scramble for money and power by Tamas's supposed allies: the Church, workers unions, and mercenary forces. It's up to a few. . . Stretched to his limit, Tamas is relying heavily on his few remaining powder mages, including the embittered Taniel, a brilliant marksman who also happens to be his estranged son, and Adamat, a retired police inspector whose loyalty is being tested by blackmail. But when gods are involved. . . Now, as attacks batter them from within and without, the credulous are whispering about omens of death and destruction. Just old peasant legends about the gods waking to walk the earth. No modern educated man believes that sort of thing. But they should. . . Winner of the David Gemmell Morningstar Award for Best Debut Fantasy.